A pneumonia caused by Pneumocystis jiroveci: highresolution computed tomography features at stages of process development (Texas Journal of Medical Science, 2024)
Pneumocystis jiroveci pneumonia is a common opportunistic infection affecting immunosuppressed patients. High-resolution CT may be indicated for evaluation of immunosuppressed patients with suspected pneumonia and normal chest radiographic findings. The most common highresolution CT finding of Pneumocystis jiroveci pneumonia is diffuse ground-glass opacity. Computed tomographic features of pneumonia caused by Pneumocystis jiroveci depend on the stage of the process. High-resolution computed tomography should be used